Human hair biochar to remove malachite green dye and bisphenol-A contamination - M. Kamaraj; P. Kamali; R. Kaviya; K. Abishek; B. Navinkumar; T.G. Nithya; L.S. Wong; J. Aravind (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Exposure to endocrine-disrupting chemicals and organic dye pollution is associated with an increased risk of toxicity, hazard, and cancer due to their widespread use. Exogenous endocrine disruptors are responsible for interfering with reproduction and development because they can either stimulate or decrease endogenous hormone responses. This work explores the feasibility of human hair biochar as a potential adsorbent for possible solid waste management processes to minimize environmental pollution. Malachite green and bisphenol-A were selected as model pollutants, and the response surface methodology was used to identify the maximal removal of these hazardous substances.METHODS: Samples of human hair waste are collected and processed. After air drying for 24 hours, it was carbonized in a hot air oven at 200 degrees Celsius for 3 hours to obtain the human hair biochar. The biochar was subjected to various instrumental analyses to ascertain the characteristics of the biochar. Both malachite green and bisphenol-A adsorption experiments are performed in a batch method. Initial pollutant concentration (100 milligrams per liter), the volume of pollutant solution (50 milliliters), temperature (37 degrees Celsius), and agitation speed of orbital shaker (150 rotation per minute) are established as constants in this investigation. Data obtained from an Ultra Violet-Visible spectrophotometer was used to design expert software to calculate adsorption efficiency.  Data variables A, B, and C included the potential of hydrogen (3, 6, 9), duration (60, 150, 240 minutes), and adsorbent dose (0.1, 0.3, 0.5 gram per liter) in the Response Surface Methodology experiment.FINDINGS: The human hair biochar is characterized by analytical methods, and Brunauer, Emmett, and Teller analysis revealed that it has a porous nature and extensive surface area, an amorphous structure, and various functional groups. The efficiency of adsorbent investigated over Malachite green and bisphenol-A in a batch experiment and performance variation of three parameters: A: potential of hydrogen (3, 6, 9), B: duration (60, 150, 240 minutes), and C: Human hair biochar dose (0.1, 0.3, 0.5 gram per liter) were evaluated via box-behnken design. Through analysis of variance and numerical expectation, the optimal potential of hydrogen, duration, and Human hair biochar dose was predicted as 3, 150 minutes, and 0.5 grams per liter, which resulted in a maximum removal of 96 percent for malachite green and 83 percent for bisphenol-A.CONCLUSION: This study demonstrated the facile heat-assisted development of biochar from human hair waste as a potential candidate for environmental remediation. The topography, structure, surface area, and functional group analysis of human hair biochar were carried out using analytical techniques that reveal the biochar has the potential for adsorbent characteristics. The adsorption efficiency of human hair biochar was demonstrated for malachite green (96 percent) and bisphenol-A (83 percent) response surface methodology under optimal conditions. The results suggested the model's relevance for the sorption of dyes and contaminants. The current study concludes that biochar can be prepared using a less expensive method and can be an alternate option to remove the dyes and other emerging contaminants in the aqueous matrix.